MAL62 overexpression and NTH1 deletion enhance the freezing tolerance and fermentation capacity of the baker's yeast in lean dough. Issue 1 (December 2016) - Sun, Xi; Zhang, Cui-Ying; Wu, Ming-Yue; Fan, Zhi-Hua; Liu, Shan-Na; Zhu, Wen-Bi; Xiao, Dong-Guang
Abstract Background Trehalose is related to several types of stress responses, especially freezing response in baker's yeast (Saccharomyces cerevisiae ). It is desirable to manipulate trehalose-related genes to create yeast strains that better tolerate freezing-thaw stress with improved fermentation capacity, which are in high demand in the baking industry. Results The strain overexpressingMAL62 gene showed increased trehalose content and cell viability after prefermention-freezing and long-term frozen. Deletion ofNTH1 in combination ofMAL62 overexpression further strengthens freezing tolerance and improves the leavening ability after freezing-thaw stress. Conclusions The mutants of the industrial baker's yeast with enhanced freezing tolerance and leavening ability in lean dough were developed by genetic engineering. These strains had excellent potential industrial applications.